Psychotherapy Supportive Practice For Borderline Personality Disorder (A Clinical Module Development) - Wardani, SpKJ, Natalia Dewi; Widiastuti, M I; Sudiyanto, Aris -; Hardian, Hardian -; Lukman, Petrin Redayani; Septiawan, Debree -; Primada, Lyla Fitrania; Uminah, Uminah -; Rasyad, Ula Faza Nayli (Journal of Biomedicine and Translational Research, 2024)
ABSTRACTBackground: Handling patients with Borderline Personality Disorder (BPD) who are hypersensitive to rejection, have unstable interpersonal relationships, self-image, affect, and behavior is a challenge for a psychiatrist. Supportive psychotherapy is one of the most widely mastered psychotherapy modalities in psychiatric education in Indonesia and is most widely practiced in psychiatric services.Objective: It is hoped that the development of a supportive psychotherapy clinical practice module for Borderline Personality Disorder will be helpful for psychiatrists in the handling of Borderline Personality Disorder patient.Methods: This research was conducted in three stages. Stage 1 was preparing the supportive psychotherapy module for 13 weeks. Stage 2 was for the module validation using face validity and content validity by two psychotherapy consultants. Stage 3 was the trials of the developed modules, where 2 interrater therapists applied the modules to treat 5 patients.Result: The face validity of the two experts for the supportive psychotherapy module for Borderline Personality Disorder in Indonesian language was 3.269, meaning that it mostly was done correctly. The results of the content validity of the two experts for the supportive psychotherapy module for Borderline Personality Disorder in Indonesian language was 81.165. The results of the two experts' face validity and content validity scores inferred that the supportive psychotherapy module for Borderline Personality Disorder in Indonesian language was suitable for use in services.Conclusion: Supportive psychotherapy module in Indonesian language for BPD is acceptable to be applied to treat Borderline Personality Disorder patients.